Fertigation for Citrus Trees - Mongi Zekri; Arnold Schumann; Tripti Vashisth; Davie Kadyampakeni; Kelly T. Morgan; Brian J. Bowman; Thomas A. Obreza (EDIS, 2017)
Microirrigation is an important component of citrus production systems in Florida. For citrus trees, microirrigation is more desirable than other irrigation methods for several reasons: water conservation, fertilizer management efficiency, and freeze protection. Research has shown that when microirrigation systems are properly managed, water savings can amount to as much as 80% compared with subirrigation and 50% compared with overhead sprinkler irrigation. Research has also shown the important advantage of microsprinklers for freeze protection of citrus. This 4-page fact sheet discusses fertilizer solubility and some common fertigation materials. It also offers a fertigation summary. Written by Mongi Zekri, Arnold Schumann, Tripti Vashisth, Davie Kadyampakeni, Kelly Morgan, Brian Boman, and Tom Obreza, and published by the UF Horticultural Sciences Department, September 2017.